PHILOSOPHICAL IDEAS IN SPIRITUAL CULTURE OF THE INDIGENOUS PEOPLES OF NORTH AMERICA - S. V. Rudenko; Y. A. Sobolievskyi (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
The purpose of the article is to reveal philosophical ideas in the mythology and folklore of the indigenous peoples of North America. An important question: "Can we assume that the spiritual culture of the American Indians contained philosophical knowledge?" remains relevant today. For example, European philosophy is defined by appeals to philosophers of the past, their texts. The philosophical tradition is characterized by rational argumentation and formulation of philosophical questions that differ from the questions of ordinary language. However, the problem lies in the term "philosophy", which belongs to the so-called "philosophical untranslatability" and has many definitions. The question of whether philosophy is exclusively a phenomenon of European culture is still controversial. In the article, the concept of philosophy is used in a broad sense, which allows the analysis of the intellectual heritage of the culture of the indigenous people of North America for philosophical ideas. Theoretical basis of the study consists of primary sources, which are limited due to the "documentary horizon". It contains myths about the Twins, ritual rhetoric, examples of dream interpretation practices and the practical wisdom of tribal chiefs. The Chronicle of "Vallamolum", or "the Red List", testifies to the special idea of the Indians about history and their own historicity. Analysis of cosmogonical and cosmological ideas reveals the special features of the anthropological ideas of the North American Indians. Combined with the philosophical ideas of the Puritan philosophy of the settlers of New England, this analysis allows us to explore in more detail the processes of acculturation. The study uses critical literature from scholars and leading researchers of the wisdom and philosophy of Native Americans, such as Michael Yellow Bird, J. Baird Callicott, Henry Wadsworth Longfellow, Dennis H. McPherson, Lewis Henri Morgan, Thomas M. Norton-Smith, J. Douglas Rabb, Paul Radin, Jon Ewbank Manchip White. The views of early American philosophers: R. Williams, W. Penn, R. W. Emerson, on the problem of the relationship between the culture of settlers and the indigenous people of North America are noteworthy. Originality lies in the application of historical and philosophical methodology, identifying the features of philosophizing in the spiritual culture and worldview of the indigenous people of North America. Conclusions. In the conclusions, the obtained results complement the history of the origin and development of philosophical thought of the early American philosophy.